EUROPE OF CULTURES: TECHNOCRACY OR TELEOLOGY? (Journal of Teleological Science, 2023)
The article discusses the idea of European unification, a common project that plunges its roots in a travel accident that occurred in the north of France in 1706. Induced by this unforeseen event, the aim of establishing permanent arbitration and ties of cooperation between nations sovereign powers to prevent future dissension is a milestone in European history. The theme is relevant insofar as the project for the unification of Europe comprises an ideal that has shaped European politics and society for centuries. The initial attempt to create a form of supranational political integration remains fundamental for the European Union today, but it cannot be purely and simply reduced to criteria of a geopolitical, macroeconomic or technocratic nature. Faithful to its ecumenical and cosmopolitan tradition, Europe always finds itself again every time it sees itself in others. The article seeks to expose and discuss how far the deepening of the “Europe of the culture(s)” configures the teleological horizon of a task that coimplicates the hermeneutic, political and religious dimensions in the construction of the “common European home”.
Keywords: European unification; Permanent arbitration; Political and economic cohesion; Cultural integration; Teleology; Hermeneutics; Politics; Religion